The Study of the Impact of Temperature and Wind In the Southern Low Pressure Systems - mahboobeh pouratashi; mohammad moradi; ebrahim fattahi (تحقیقات کاربردی علوم جغرافیایی)
This research aims to study the impact of temperature and wind in the southern low-pressure system and its associated precipitation in the southern regions of Iran. As The southern low pressure system moves eastward, it crosses the southern regions of Iran, causing medium and heavy rainfall in these areas. In this study, two southern low-pressure systems that caused heavy rainfall on March 11, 2015 and January 17, 2000 in southern Iran were selected, analyzed and simulated using the numerical Weather Research and Forecasting (WRF) model. Since the wind and temperature fields play a significant role in the southern low-pressure systems, four experiments were performed for investigating the effects of temperature and wind on the intensification and weakening of the southern system. The simulation results showed that the simulation for the increased (decreased) temperature caused the weakened (intensified) the southern low pressure in the studied area. This result showed that the vertical structure of the southern low-pressure and its physical characteristics are similar to the mid-latitudes cyclones, and these systems were different from the thermal low pressures. The results of wind speed changes showed that the increased (decreased) wind speed simulation caused an increase (decrease) in relative vorticity, thus the southern low pressure was intensified (weakened). In both cases, the rainfall was decreased by the increased temperature simulation, and decreased temperature caused an increase in rainfall. It was also seen that the increase in wind speed caused the special humidity advection to be increased and then the rainfall increased. Also the amount of rainfall decreased when conditions did not provide for the advection of specific humidity or the wind speed reduced.